Python based location analysis of wind mills in urban environment - Hossain, Mohammad Rafayet (GeoJournal, 2021)
Identification of appropriate location for windmills in landlocked states, like the state of Iowa requires consideration of multiple factors and analysis of a large database, which is time-consuming. Under this study, advanced remote sensing and Python-based programming language have been utilized to select three specific sites within the boundaries of Lyon and Sioux county to locate new windmills based on three crucial factors; wind speed, elevation, and physicals barriers. The entire study area has been divided into several zones and ArcGIS tools, like selection, clipping, and merging have been used to process the entire database collected from secondary sources. Python scripts have been also used to calculate zone wise mean value of all three factors. Python scripts developed under this study are easily modifiable to include more than three factors providing a cost-effective method of decision making in the case of locating new windmills. An algorithm has been developed in the end section to combine all three factors and to rank all the zones considering their energy efficiency and environmental sustainability.